2011
DOI: 10.1002/jccs.201190106
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Determination of Trace Pb2+ in Seawater Using Columnar Glassy Carbon Electrode

Abstract: We herein report a mercury-free approach for the sensitive determination of trace Pb 2+ in seawater using differential pulse stripping voltammetric (DPSV) method with a novel columnar glassy carbon electrode (CGCE). Compared with the conventional disk glassy carbon electrode with the same diameter, it has much larger electrochemical area (0.627 ± 0.003 cm 2 ). The CGCE shows good accumulation ability and consequently acceptable behavior which makes it suitable as a working electrode in the DPSV determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…But as interference ions, their existence posed a threat to accuracy of detection. Zhang et al 35 found that the same concentration of Hg 2+ increased the peak current of 10 μg l −1 Pb 2+ by 28.6% in acidified artificial seawater with pH 1.36. Another research also discovered that the current response of Pb increased when 100 μg l −1 of Bi 3+ was present, as shown in Fig.…”
Section: Major Detection Interferencementioning
confidence: 99%
“…But as interference ions, their existence posed a threat to accuracy of detection. Zhang et al 35 found that the same concentration of Hg 2+ increased the peak current of 10 μg l −1 Pb 2+ by 28.6% in acidified artificial seawater with pH 1.36. Another research also discovered that the current response of Pb increased when 100 μg l −1 of Bi 3+ was present, as shown in Fig.…”
Section: Major Detection Interferencementioning
confidence: 99%